THE PRAYER OF THE NAME IN THE HINDU TRADITION - Anand, Subhash (Journal of Dharma, 2003)
Years ago some of my friends told me that a Hindu child from the neighbourhood would occasionally come and sit in their chapel while Mass was being celebrated. They did their best to get the child tell them her name, but without success. One day I was invited by them to celebrate the Eucharist for them. On seeing the child I said: “Oh Jyoti! I am so happy to meet you.” The little one was not pleased at all and so, not without some disdain, she said to me: “I am not Jyoti. I am Kiran!” That is exactly what I wanted. When I called the child by some other name, the child was upset, because deep down the little girl felt that I was confusing her for some other child and, thereby, disregarding her unique identity. Somehow our name is intimately linked with our person. This explains why “name and naming activities are central to human symbolic and communicative processes. To be human is to name, and be named, and thereby to possess full being and the ability to relate to the world in meaningful ways.